Improving lupus care index documentation in patients with childhood-onset systemic lupus erythematosus - Barbar-Smiley, Fatima A.; Yildirim-Toruner, Cagri; Akoghlanian, Shoghik; AlAhmed, Ohoud; Ardoin, Stacy P.; Leone, Ashlee; Oberle, Edward; Sivaraman, Vidya (Frontiers in Pediatrics, 2024)
Improving Lupus Care Index Documentation in Children with Childhood-onset Systemic Lupus Erythematosus (c-SLE), aligns closely with the scope of Frontiers in Pediatric Rheumatology, which emphasizes advances in clinical practices for pediatric Rheumatic Diseases. Our study details a Quality Improvement (QI) initiative at Nationwide Children's Hospital aimed at enhancing the documentation of disease assessment in patients with c-SLE. This work is directly relevant to the journal's focus on innovative methodologies and improved outcomes in pediatric rheumatology. By showcasing effective strategies for accurate disease assessment through a multidisciplinary approach, our manuscript offers valuable insights that can advance the management of pediatric lupus, aligning well with the journal's commitment to high-impact pediatric research.